2020
DOI: 10.1002/asia.202000892
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in Fluorescence Light‐Up Endogenous and Exogenous Carbon Monoxide Detection in Biology

Abstract: Considerable attention has been paid by the scientific community to detect toxic carbon monoxide (CO) in sub-cellular organelles like mitochondria, lysosomes, nuclei, etc. due to their generation and accumulation through numerous biological processes and their role as signal transducer, therapeutics, etc. Various methods are also available for detection of CO, but fluorescence light-up detection is considered the best due to its easy and accurate sensing capability. As of now, no review is available in the lit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 76 publications
0
20
0
Order By: Relevance
“…Numerous advantages, such as its nondestructive quality, convenience, deep tissue penetration, high sensitivity, and spatiotemporal resolution, render it irreplaceable for detecting intracellular biological molecules in living systems [23][24][25]. A number of fluorescent probes for the specific detection of CO have been proposed [26][27][28][29][30][31]. Chang et al reported the first organic palladium complexes' fluorescent probes (COP-1) to detect endogenous CO in 2012 [32].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous advantages, such as its nondestructive quality, convenience, deep tissue penetration, high sensitivity, and spatiotemporal resolution, render it irreplaceable for detecting intracellular biological molecules in living systems [23][24][25]. A number of fluorescent probes for the specific detection of CO have been proposed [26][27][28][29][30][31]. Chang et al reported the first organic palladium complexes' fluorescent probes (COP-1) to detect endogenous CO in 2012 [32].…”
Section: Introductionmentioning
confidence: 99%
“…Carbon monoxide (CO) generated from the incomplete combustion of fuels is generally considered one of the most toxic gases responsible for the pollution of the environment as its inhalation causes the reduction of oxygen (O 2 ) transport by hemoglobin, leading to health hazards including increased chest pain, headache, and even death, and affecting the central nervous system via impaired reaction timing (permissible limit 10-300 ppm). 1 In contrast, CO at a very low concentrations behaves as a key endogenous gaseous signal molecule, leading to a positive inuence on physiological and pathophysiological processes. [1][2][3][4] Several diseases like Alzheimer's disease, hypertension, inammation and heart failure are the result of the misregulation or abnormal metabolism of CO levels.…”
Section: Introductionmentioning
confidence: 99%
“…1 In contrast, CO at a very low concentrations behaves as a key endogenous gaseous signal molecule, leading to a positive inuence on physiological and pathophysiological processes. [1][2][3][4] Several diseases like Alzheimer's disease, hypertension, inammation and heart failure are the result of the misregulation or abnormal metabolism of CO levels. [5][6][7][8] Thus, it is important to develop very low-level CO detection to understand the physiological pathway using endogenous CO in subcellular organelles to explore its health benecial mechanism.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations